On the Utility of Longwave-Infrared Spectral Imaging for Remote Botanical Identification - David M. Tratt (Remote Sensing, 2021)
A multi-year airborne field investigation of remote botanical species identification was conducted involving multiple curated botanical collections. The purpose of the study was to better constrain the observational conditions that most favor remote identification by longwave-infrared spectral imaging and assess the degree to which confidence metrics developed for remote chemical composition determination could be adapted to botanical species classification. Identification success was examined as a function of spatial resolution and viewing obliquity. A key aim was to articulate a procedure for validating inferred species identifications and evaluating the retrieval methodology’s performance for alleviating confusion between species exhibiting spectral similarity at the foliar scale. It was found that several confounding factors degrade confidence in the species identifications to levels that render the approach impractical in the general case. A number of taxa, predominantly evergreen, were nevertheless identified that are amenable to the technique and for which utility may be viable.